2016
DOI: 10.1680/macr.15.00097
|View full text |Cite
|
Sign up to set email alerts
|

Stability and instability of foamed concrete

Abstract: Foamed concrete has proven to be an effective alternative to granular fills and is now widely used internationally. With increasing demand for lightweight materials for buildings in order to improve sustainability, foamed concrete has also developed as an ideal material for this purpose, and many countries utilise construction with precast foamed concrete blocks. However, at densities lower than current technology allows, typically <500 kg/m 3 , foamed Magazine of Concrete Research Volume 68 Issue 11 Jones, Oz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(57 citation statements)
references
References 8 publications
4
52
0
1
Order By: Relevance
“…As compared with solids, it is a composite of air voids and hardened cement paste or mortar. In extremity, the air content can be higher than 85% [1]. Due to its high porosity, the foam concrete density ranges from 0.3 to 1.6 g/cm 3 [2], leading to a low strength ranging between 30 and 1500 psi [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As compared with solids, it is a composite of air voids and hardened cement paste or mortar. In extremity, the air content can be higher than 85% [1]. Due to its high porosity, the foam concrete density ranges from 0.3 to 1.6 g/cm 3 [2], leading to a low strength ranging between 30 and 1500 psi [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that foam concrete with fine aggregates shows a greater tendency of shrinkage, and ensuring good curing is critical [12,22]. It is generally understood that greater sand or particle content reduces the foam stability, which usually causes strength reduction in foam concrete [18,[23][24][25]. For most cases, a small amount of inclusion of finer particles results in a higher strength of foam concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to addition of gas-forming chemicals, the use of foaming agents in producing the foam concrete has a higher potential for application in 3D-printing. This is mostly explained by the fresh and hardened properties' relative ease of adjustment by varying row materials and chemical admixtures [1,2,21,23,32,33].…”
Section: Introductionmentioning
confidence: 99%